2003
DOI: 10.1159/000069010
|View full text |Cite
|
Sign up to set email alerts
|

Expansion and Proliferation of Skin-Homing T Cells in Atopic Dermatitis as Assessed at the Single Cell Level

Abstract: Background: Sensitization to aeroallergens is a frequent event in patients with atopic dermatitis (AD). The role of allergen-specific T cells in the pathogenesis of AD is, however, not fully clear. A detailed immunological characterization of allergen-specific T cells able to migrate to inflamed skin might therefore be helpful in determining the relevance of allergen-specific T cells to clinical symptoms. Objective: To establish a simple assay to simultaneously monitor the expression of skin-related homing mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…8, 911 Most T-cells in AD lesions are CD45RO + memory cells that express the skin-homing receptor cutaneous lymphocyte antigen (CLA). 1214 Circulating CLA + T-cells are expanded in AD, respond to skin-associated allergens, and play a role in disease pathogenesis. 1417 CLA + T-cells have been also demonstrated to be peripheral biomarkers in several inflammatory skin diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8, 911 Most T-cells in AD lesions are CD45RO + memory cells that express the skin-homing receptor cutaneous lymphocyte antigen (CLA). 1214 Circulating CLA + T-cells are expanded in AD, respond to skin-associated allergens, and play a role in disease pathogenesis. 1417 CLA + T-cells have been also demonstrated to be peripheral biomarkers in several inflammatory skin diseases.…”
Section: Introductionmentioning
confidence: 99%
“…1214 Circulating CLA + T-cells are expanded in AD, respond to skin-associated allergens, and play a role in disease pathogenesis. 1417 CLA + T-cells have been also demonstrated to be peripheral biomarkers in several inflammatory skin diseases. 18 The need for large biopsies to classify T-cell subsets limits the feasibility of intracellular cytokine staining (ICS) of skin from adults and even more so in children.…”
Section: Introductionmentioning
confidence: 99%
“…Most T cells in AD skin lesions are CLA + CD45RO + memory cells . Circulating CLA + T cells are expanded in AD, respond to skin‐associated allergens, infiltrate skin lesions, and are central players in the initiation and perpetuation of AD lesions . Additionally, it has been shown that bacterial toxins increase CLA expression in superantigen‐mediated diseases and that AD severity is correlated with CLA + T‐cell‐attracting chemokines in serum .…”
mentioning
confidence: 99%
“…Allergen-reactive T cells derived from patients with AD are predominantly CD4 þ T cells which express the skinhoming marker, cutaneous lymphocyte-associated antigen (CLA), suggesting a direct function of these cells in the disease (Santamaria Babi et al, 1995;Jung et al, 2003). Despite this, few studies of AD patients have examined T cell responses in allergen-specific systems.…”
mentioning
confidence: 99%